2005
DOI: 10.1016/j.actamat.2005.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Incipient plasticity during nanoindentation at grain boundaries in body-centered cubic metals

Abstract: The mechanical response to nanoindentation near grain boundaries has been investigated in an Fe-14%Si bicrystal with a general grain boundary and two Mo bicrystals with symmetric tilt boundaries. In particular, the indentations performed on the Fe-14%Si show that as the grain boundary is approached, in addition to the occurrence of a first plateau in the load versus depth nanoindentation curve, which indicates grain interior yielding, a second plateau is observed, which is believed to indicate dislocation tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(90 citation statements)
references
References 41 publications
3
83
1
1
Order By: Relevance
“…Micro-hardness experiments indicate that segregation of solute atoms at the GBs results in either hardened or softened regions compared to the interior of the adjacent grains [11,12]. Nanoindentation has detected a significant increase in the intrinsic hardness of the material near the GBs due to dislocation pinning [13][14][15][16][17][18]. In situ nanoindentation measurements during electrochemical exposures of metals at cathodic potentials revealed near-surface softening due to absorbed hydrogen [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Micro-hardness experiments indicate that segregation of solute atoms at the GBs results in either hardened or softened regions compared to the interior of the adjacent grains [11,12]. Nanoindentation has detected a significant increase in the intrinsic hardness of the material near the GBs due to dislocation pinning [13][14][15][16][17][18]. In situ nanoindentation measurements during electrochemical exposures of metals at cathodic potentials revealed near-surface softening due to absorbed hydrogen [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GB pop-ins were not observed in interstitial-free steel or in fcc copper, but were observed in commercial steel with interstitials. Soer et al 62,67 studied grain boundaries in Fe-14%Si and Mo bicrystals and reported consistent GB pop-ins in Fe-14%Si, but not in Mo. Aifantis et al 65 also reported GB pop-ins in Fe-2.2%Si bicrystals.…”
Section: Grain/phase Boundaries In Metalsmentioning
confidence: 98%
“…Interestingly, the incipient pop-ins have been observed to be suppressed or mitigated in indentations conducted close to the grain boundary (compared to those conducted in the grain interior). 24,[60][61][62][63] These observations have suggested that the grain boundaries serve as potent sources of dislocations.…”
Section: Grain/phase Boundaries In Metalsmentioning
confidence: 99%
See 2 more Smart Citations